Food Futures : Sensory Explorations in Food Design - Sweetapple, Kate; Warriner, Gemma (Barcelona : Promopress Editions, 2017)
Jeon, Jinhyun ; Groß, Benedikt ; Nendo ; Okamoto, Maki ; Zahareas, Louisa ; Vogelzang, Marije ; Space10 ; Keville Joyce, Anna & Zarebinski, Lucas ; Mugita, Keizo & Tanino, Kazuya & Chino, Toru ; Knoppert, Louise ; Kinneir, Simon ; Nur Saltik, Bilge ; Tsopanides, Johannes ; Edvard, Jonas ; Monté, Isaac ; Zimmer, Tobias ; Bertille & Mathieu ; Baltz, Emilie & Diana, Carla & Dyer, Arone ; Honey and Bunny ; Wijnsma, Jouw & Kullik, Martin ; Baltz, Emilie ; Almqvist, Sofia ; Gong, Paul ; Museum of Food and Drink (MOFAD) ; Golik, Martyna Barbara ; Brown, Matt ; Nichols, Anabelle ; Livin Studio ; Rutzerveld, Chloé ; Rael, Ronald & San Fratello, Virginia ; Wist, Ally ; Park, Celine ; KaCaMA Design Lab ; Sawa, Marin ; The Tangible Media Group at the MIT Lab ; de Waal, Caro ; Kim, Minsu ; Krnáčová, Terézia ; van Zanten, Lisanne ; Silver, Tim ; Tokuyasu, Tomomi
boek